Public awareness on corruption among household in Vista Ilmu, Kota Samarahan / Mohamad Naqiuddein Hamzah & Muhamad Nabil Zamzuri - Hamzah, Mohammad Naqiuddein; Zamzuri, Muhamad Nabil (2017)
This study is about public awareness and perception on corruption. This study is conducted based on the previous study by Bowman and Gilligan (2007) entitled “Public Awareness on Corruption in Australia”. In this chapter, there are seven (7) sections included. The first section (Section 1.1) will discussed shortly on the background of this study. In the second section (Section 1.2), the problem statement will be explained and the third section (Section 1.3) will identified all research question. Next, (Section 1.4) will specified on the research objective while in (Section 1.5) is focused on the scope of this study. After that, (Section 1.6) will show more regarding the significance of the study. Last but not least, section 7 (1.7) will explained more on the definitions of key terms.